A Method for Minimizing the Control Calculation Time of Fractional Systems - Hcheichi, Khaled; Bouani, Faouzi (Journal of Applied Nonlinear Dynamics, 2026)
This article deals with the non-commensurate fractional systems represented by a state-space model. It presents the advantages and disadvantages of using this type of model. It focuses on the disadvantages of fractional systems, especially the increase of computing time due to the accumulation of history. A method is proposed to minimize the calculation time, it consists in limiting the use of history of the state variables to a reduced number and taking into account the uncertainty of model in the predictive control. This method will be compared to the classical method in term of performance and calculation time.